A Medal for Benny Movie Still - Paramount Pictures:::Creator::::::::::::
Charlie Martin (J. Carrol Naish) just after being told of his son's heroism and resulting death in Paramount Pictures 1945 production of 'A Medal for Benny.' From left: Chito Sierra (Fernando Alvarado), Mayor of Pantera (Grant Mitchell), Charlie Martin, Joe Morales (Arturo de Cordova), Lolita Sierra (Dorothy Lamour). According to caption, the production company was giving Lamour and de Cordova an opportunity to show their talents with this movie. This exact shot is not in the movie.